KIPÇAK GRUBU TÜRK LEHÇELERİNDE ÇOKLUK VE BİRLİKTELİK BİLDİREN İFADELER - ALEVSAÇAN, ALEYNA (Fırat Üniveristesi, 2025)
Varlıkların birden fazla olma durumunu belirten çokluk kavramı, genellikle sayısal bir çokluk olarak algılanmasına rağmen aslında sayısız ve belirsiz bir çokluğu ifade etmektedir. Çokluk kavramı dillerde ekler, sözcükler ve sözcük grupları gibi farklı yapılarla kurulan özel kategorilerdir. Birçok dilde olduğu gibi Türkçede de sayısız ve belirsiz bir çokluk bulunmaktadır. Çokluk kategorisi bu anlamda belirsiz bir nicelik çokluğunu kapsamakla birlikte kavramsal anlamdaki belirsiz bir çokluğu da karşılamaktadır. Türkçe çokluk bildiren ekler bakımından çeşitlilik gösteren zengin bir dildir. Hem tarihî dönemlerde hem de çağdaş devirlerde Türk dilinin (Çuvaş Türkçesi hariç) yaygın olarak kullanılan çokluk eki +lAr'dır; ancak Türkçenin eski yazılı metinlerinden itibaren tanıklanan ve sözcüklerin kök veya gövdeleriyle kaynaştığı için çokluk eki işlevini yitirmiş olan birçok çokluk işlevli ekin varlığı, Türkçenin çokluk eki açısından zengin bir dil olduğunun göstergesidir. Eski Türkçe döneminden itibaren +lAr, +GUn, +gil, +An, +z, +t, +k, +ş, +n, +l, +r ve +s eklerinin çokluk eki olarak kullanıldığı görülür. Türk dilinin tarihî ve çağdaş lehçelerinde bu eklerden +lAr çokluk eki yaygın olarak kullanılmaktadır. Öyle ki, +lAr eki dışındaki çokluk ekleri zamanla ya tamamen kullanımdan düşmüş ya da belli kelimelerle kaynaşarak varlıklarını kısmen korumuşlardır. Çoklukla ilgili yazılmış çoğu şey

The concept of plural, which indicates the state of being more than one, is generally perceived as a numerical multiplicity, but in fact it expresses an innumerable and indefinite multiplicity. The concept of plural is a special category established with different structures such as suffixes, words and word groups in languages. As in many languages, there is an innumerable and indefinite multiplicity in Turkish. In this sense, the category of plural includes an indefinite quantity multiplicity, but it also corresponds to an indefinite multiplicity in the conceptual sense. Turkish is a rich language that shows diversity in terms of plural suffixes. The plural suffix commonly used in Turkish (except for Chuvash Turkish) both in historical periods and in contemporary periods is +lAr; however, the existence of many plural suffixes that have been witnessed since the old written texts of Turkish and have lost their plural function because they have merged with the roots or stems of words is an indication that Turkish is a language rich in terms of plural suffixes. Since the Old Turkish period, the suffixes +lAr, +GUn, +gil, +An, +z, +t, +k, +ş, +n, +l, +r and +s have been used as plural suffixes. In the historical and contemporary dialects of the Turkish language, the plural suffix +lAr is widely used. In fact, plural suffixes other than the +lAr suffix have either fallen out of use completely over time or have partially preserved their existence by merging with certain words. Most writings on pluralism generally focus on plural suffixes; however, some studies also consider word types and certain word groups, such as adjectives, pronouns, and reduplications, in addition to suffixes. This study examines and classifies structures in which plurals are used not only as suffixes but also as words in the Kipchak group of Turkish dialects, and examines their commonalities in terms of plurals and conjunctions. Keywords: Multiplicity, Unity, Kipchak group of Turkic Dialects
Expressions indicating multiplicity and unity in the Kypchaq group of Turkic dialects
Keywords: Dilbilim